Kepemimpinan dalam Konteks Pendidikan Islam - Alya Dinia Asyfiqi Masykur; Sunarto Sunarto (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The purpose of this study is to describe leadership in Islamic education. This study uses qualitative with a library research method. The results of this study indicate that Islamic Education leadership means Educational leadership as a determinant of the success of all activities in the Islamic Education institution. The concept of leadership in Islam has been mentioned in the Qur'an, expressed in various terms, namely Caliph, Imam, and Ulil Amri. The characteristics that must be possessed by Islamic Education leadership refer to the characteristics of the leadership of the Prophet Muhammad, namely shidiq, amanah, fathonah, and tabligh. The last is the leadership style in Islamic Education, namely autocratic, participatory or democratic leadership style, Laizess faire, transformative, paternalistic, and militaristic.